(untitled) - Peterson, Tracie; Miller, Judith; 1944- (BethanyHouse Publishers, 2005)
"When tragedy strikes, Jasmine Houston must uproot her family from the Northern mill town of Lowell and take over her family's Southern plantation. Tensions are high, and the lives of the slaves they've promised to protect hang in the balance"--Provided by publisher.
Keywords: Fiction; Slavery; Fiction; Fiction; Women plantation owners; Plantation life; Southern States; Fiction; Historical fiction; Christian fiction